2023
DOI: 10.3390/su15032559
|View full text |Cite
|
Sign up to set email alerts
|

E-Health Research in Southeast Asia: A Bibliometric Review

Abstract: eHealth or digital health innovations expanded tremendously during the COVID-19 pandemic. Innovation and digitalization offer creative solutions to build up a healthy society. The eHealth technologies are quickly taken up by Southeast Asia countries and continue to flourish to alleviate the burden of healthcare challenges. This study is the first review exploring and analyzing the whole literature of eHealth, specifically in the Southeast Asia region. The objective of this study is to document the size, growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Region-specific bibliometric reviews demonstrated global interest in eHealth research. Published reviews covered medical informatics and telemedicine in Sub-Saharan Africa and BRICS countries [20], eHealth research in Southeast Asia [21], and European finding of research on ambient assisted living [22].…”
Section: Affiliations Introductionmentioning
confidence: 99%
“…Region-specific bibliometric reviews demonstrated global interest in eHealth research. Published reviews covered medical informatics and telemedicine in Sub-Saharan Africa and BRICS countries [20], eHealth research in Southeast Asia [21], and European finding of research on ambient assisted living [22].…”
Section: Affiliations Introductionmentioning
confidence: 99%
“…In recent years, bibliometrics has emerged as a preferred method for conducting literature reviews in various research fields. Some examples include corrosion in medical implants [10], e-health initiatives [11], future-oriented green communication [12], blockchain applications [13], smart healthcare systems [14], and the Internet of Things (IoT) in healthcare settings [15].…”
mentioning
confidence: 99%